Analisis Pengaruh Pajak Daerah Terhadap Pendapatan Asli Daerah (PAD) Kota Manado Tahun 2003 - 2011 - Moningka, Petrus (JBE (Journal of Business and Economics); Volume 11 No.1, 2012 JBE UNKLAB, 2012)
This research has the purpose to examine how big local taxation influences to Local Own Revenues (PAD) of Manado City. Local taxation used in this study are Hotel and Restaurant taxation. The research outcome indicates that the growth of Hotel and Restaurant taxation is bigger than Local own revenues  and has a big contribution toward Local own revenues  of Manado City in 2003-2011.  The hypothesis testing partially by using simple regression analysis, either Hotel taxation or Restoran taxation significantly influences to local own revenues likewise, the testing by using multiple regression analysis indicates that Hotel and Restaurant taxation positively influence and significant to Local own revenues  of Manado City.